Sistema Interno de adquisiciones (compras públicas) para la Empresa Eléctrica Regional del Sur (EERSSA) mediante el uso de la Herramienta Genexus. - Herrera Salazar, Valaria del Rosario (2011)
This research work aims at the development of an internal Procurement (Public Procurement) for the Southern Regional Electricity Company (EERSSA), whichoptimizes the procurement process prior to being uploaded to the Portal of Public Procurement with all threads that carry the same such as the development and approval of applications, certificates, envelopes, resolutions and memorandum which may bemade depending on the functions which each system user. In addition to optimizing thetime in the development of this process, the system improves the image of the institution, it is important that the institution is kept up to date on the importance that is taking the technological development within the business field.